2022
DOI: 10.1001/jamainternmed.2021.8075
|View full text |Cite
|
Sign up to set email alerts
|

Assessing How Consumers Interpret and Act on Results From At-Home COVID-19 Self-test Kits

Abstract: IMPORTANCEThe US Food and Drug Administration (FDA) authorized SARS-CoV-2 rapid at-home self-test kits for individuals with and without symptoms. How appropriately users interpret and act on the results of at-home COVID-19 self-tests is unknown.OBJECTIVE To assess how users of at-home COVID-19 self-test kits interpret and act on results when given instructions authorized by the FDA, instructions based on decision science principles, or no instructions. DESIGN, SETTING, AND PARTICIPANTSA randomized clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…First, there is a significant need for educational campaigns to build lay user trust in the accuracy of at-home antigen tests and knowledge around when and how to use them, including how to act on test results [ 26 ]. Of the seven constructs that comprise acceptability, coherence and perceived effectiveness were most salient and determined whether participants ultimately felt it “was worth it” to test for COVID-19 daily.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a significant need for educational campaigns to build lay user trust in the accuracy of at-home antigen tests and knowledge around when and how to use them, including how to act on test results [ 26 ]. Of the seven constructs that comprise acceptability, coherence and perceived effectiveness were most salient and determined whether participants ultimately felt it “was worth it” to test for COVID-19 daily.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be speculated that people who tested positive with a self-test and did not report it, were less compliant with the isolation requirement than those who were provider-tested. However, the results of the APB survey seem to indicate that people are well aware that they should isolate if the self-test is positive, as other research has also shown [27].…”
Section: Number Of Reported Positive Self-testsmentioning
confidence: 78%
“…These results complement recent data on how consumers act on the results of at-home COVID-19 self-test kits. 14 …”
Section: Discussionmentioning
confidence: 99%